Financial Leverage and its Relationship with Financial Strength, Growth and Capital Intensity in Companies Listed on Tehran Stock Exchange (Linear & Curvilinear Relationships) - Esmail Tavakolnia (راهبرد مدیریت مالی, 2014)
Decision making about capital structure is one of the most difficult and challenging issues facing companies. The capital structure of a business is the mix of types of debts and equities the company has on its balance sheet. The main purpose of this study is to examine the potential curvilinear relationship between capital intensity and financial leverage in the companies listed on Tehran Stock Exchange. Also, this study examines the relationship between financial strength, growth and financial leverage. The sample of this study, includes 110 companies listed on the Tehran Stock Exchange during the period 2007-2011 and for processing and testing hypotheses, regression method has been employed. The study finds no evidence of the impact of growth on the financial leverage and positive impact of financial strength on the financial leverage. Moreover, the findings support the U-shaped relationship between capital intensity and financial leverage in the companies listed on Tehran Stock Exchange